MIMO Channel Modeling for Tunnel Based on Directive Scattering Model and Ray Tracing - Rongchen Sun; Zhenyu Yi; Liu Liu; Zhiguo Sun; Tao Zhou (International Journal of Antennas and Propagation)
In this paper, semideterministic multi-input multi-output (MIMO) channel modeling is proposed for a tunnel with two types of cross sections. To be more consistent with the MIMO propagation characteristics of the measured data, ray tracing (RT) is used to simulate the specular components (SCs) and a directed path channel modeling method based on directive scattering model (DSM) is used to simulate the diffuse components (DCs), which has an important contribution in MIMO channel capacity. The performance of the proposed model is compared in terms of delay domain, angle domain, and channel capacity. By analyzing the DSM and the propagation graph based on the Lambertian scattering model (LSM), it was demonstrated that the proposed method is more suitable in terms of comprehensive performance.